2016
DOI: 10.1038/npjamd.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-520d-5p promotes survival in human dermal fibroblasts exposed to a lethal dose of UV irradiation

Abstract: We previously reported that hsa-miR-520d-5p is functionally involved in the induction of the epithelial–mesenchymal transition and stemness-mediated processes in normal cells and cancer cells, respectively. On the basis of the synergistic effect of p53 upregulation and demethylation induced by 520d-5p, the current study investigated the effect of this miRNA on apoptotic induction by ultraviolet B (UVB) light in normal human dermal fibroblast (NHDF) cells. 520d-5p was lentivirally transfected into NHDF cells ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…13 In the present study, we found that baicalin increased cell viability ( Figure 1A) and suppressed apoptosis (Figure 2A and B) of human fibroblast cells induced by UVB at 600 J/m 2 , the dose level high enough to caused fibroblast cells to undergo apoptosis. 39,40 UVB radiation is capable of activating several apoptotic pathways by inducing DNA damage and activating tumor suppressor gene p53. 24 As UVB radiation activates p53 signaling pathway, the downstream proapoptotic Bax is upregulated and anti-apoptotic Bcl-2 is suppressed, leading cell arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the present study, we found that baicalin increased cell viability ( Figure 1A) and suppressed apoptosis (Figure 2A and B) of human fibroblast cells induced by UVB at 600 J/m 2 , the dose level high enough to caused fibroblast cells to undergo apoptosis. 39,40 UVB radiation is capable of activating several apoptotic pathways by inducing DNA damage and activating tumor suppressor gene p53. 24 As UVB radiation activates p53 signaling pathway, the downstream proapoptotic Bax is upregulated and anti-apoptotic Bcl-2 is suppressed, leading cell arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also found two key miRNAs (miR-520d-5p and miR-139-5p). Previous studies have found that miR-520d-5p can promote the survival of human dermal broblasts exposed to a lethal dose of ultraviolet radiation (20). Undifferentiated collagen-bound miR-520d-5p has anti-tumor effect on undifferentiated cancer cells in a mouse xenograft model (21).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies so far demonstrated that miR-520d-5p participates in diverse cellular processes. In human dermal fibroblast (NHDF) cells, miR-520d-5p repairs damages induced by ultraviolet B and restore damaged cells to normal senescent state through the survival of CD105-positive cells via c-Abl-ATR-BRCA1/p53 signaling pathways [ 37 ]. Given its anti-tumor effect, miR-520d-5p suppresses human glioma cell proliferation through targeting PTTG1 [ 38 ] and inhibits tumor metastasis and growth by binding to CTHRC1 in colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%